A STATE-OF-THE-ART REVIEW OF BACKGROUND KNOWLEDGE AS ONE OF THE MAJOR FACTORS THAT INFLUENCE READING COMPREHENSION PERFORMANCE - Lahuerta Martínez, Ana Cristina (ELIA: Estudios de Lingüística Inglesa Aplicada, 2017)
Abstract The aim of this paper is to review the research carried out to date on the use and effect of background knowledge on reading comprehension. We want to reflect on the use of background knowledge in first (L1) and second (L2) language reading comprehension and on the interrelation between language proficiency and background knowledge in reading comprehension performance. This study aims to provide more insight into the relationship between prior knowledge and reading comprehension, which will add to the knowledge of reading research and will help better understand the role of these factors and how they affect one another. Resumen El objetivo de este artículo es revisar la investigación que se ha llevado a cabo hasta la fecha acerca del uso y efecto del conocimiento previo en la comprensión escrita. Queremos reflexionar sobre el uso del conocimiento previo en la comprensión lectora en una lengua nativa y en una segunda lengua, así como sobre la interrelación entre la competencia lingüística y el conocimiento previo en la comprensión lectora. Este estudio pretende profundizar en la relación entre el conocimiento previo y la comprensión lectora, lo que incrementará el conocimiento de la investigación llevada a cabo en el campo de la lectura y ayudará a entender mejor el papel de estos factores y qué efecto tienen entre sí.